Comparative study of two degree-of-freedom rotary-linear machines with permanent-magnet mover for high dynamic performance - He, Yaojie (2023)
This paper analyzes and evaluates various topologies of yokeless rotary-linear (RL) machine with permanent-magnet (PM) mover targeting for the achieving high dynamic performance. For the conventional yokeless RL machines, the single-stator topology features limited slot area for armature winding excited for both motions, and the coupled magnetic fields of both motions requires complex control strategy. In order to mitigate these issues, a double-stator RL machine with hybrid PMs array, which adopts the PMs with six magnetization directions, is proposed in this paper. An improved PMs array is introduced for the double-stator topology to achieve decoupled control for both motions. In addition, an analytical model of the radial flux density is derived to reveal the characteristics of the magnetic fields in different topologies. The parametric studies towards key dimensions are conducted to provide design guidelines and obtain the optimal design. Finally, the electromagnetic performances of the proposed design are compared systematically with the conventional single-stator counterparts. It is revealed that the proposed topology can enhance the performances in both motions, namely rotary and linear motions.